2020
DOI: 10.3390/ma13163651
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rare Earth Element (Y) on Microstructure and Corrosion Behavior of Hot Extrusion AZ91 Magnesium Alloy

Abstract: The influence of rare earth element (RE) Y on the microstructure and corrosion behavior of extruded AZ91 Mg alloy was surveyed via morphology characterization and corrosion performance measurements. The results indicate the corrosion resistance of the transversal section of AZ91 Mg alloy containing Y was improved compared with AZ91 Mg alloy without Y. The corrosion resistance of the longitudinal section of AZ91 Mg alloy with Y was lower than that of AZ91 Mg alloy without Y. The change of corrosion resistance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…However, the cast RE1 alloy (containing 1 wt-% RE) exhibited a remarkably better corrosion resistance than the RE0 alloy (containing 1 wt-% Sr) owing to the better effect of RE elements on the modification of β phase and also lower Volta-potential values of the Al 11 RE 3 particles compared to that of the Al 4 Sr phase. Furthermore, previous studies showed that the RE elements could assist the formation of a more compact RE-containing corrosion layer, resulting in the improvement of the corrosion resistance of AZ91 alloy [20,24,25]. Thus, for another reason, the RE-containing alloys showed better corrosion resistance than the Srcontaining alloys.…”
Section: The Results In Tablementioning
confidence: 96%
See 1 more Smart Citation
“…However, the cast RE1 alloy (containing 1 wt-% RE) exhibited a remarkably better corrosion resistance than the RE0 alloy (containing 1 wt-% Sr) owing to the better effect of RE elements on the modification of β phase and also lower Volta-potential values of the Al 11 RE 3 particles compared to that of the Al 4 Sr phase. Furthermore, previous studies showed that the RE elements could assist the formation of a more compact RE-containing corrosion layer, resulting in the improvement of the corrosion resistance of AZ91 alloy [20,24,25]. Thus, for another reason, the RE-containing alloys showed better corrosion resistance than the Srcontaining alloys.…”
Section: The Results In Tablementioning
confidence: 96%
“…Furthermore, previous studies showed that the RE elements could assist the formation of a more compact RE-containing corrosion layer, resulting in the improvement of the corrosion resistance of AZ91 alloy [20,24,25]. Thus, for another reason, the RE-containing alloys showed better corrosion resistance than the Sr-containing alloys.…”
Section: Resultsmentioning
confidence: 99%
“…RE elements can improve the mechanical strength and creep resistance ( Cui et al, 2020 ), refine the grain, and synthesize precipitated phases. RE elements, such as Y, lead to the formation of a protective antioxidant film on the surface of the Mg matrix after heat laser fabrication; WE43 alloys demonstrate excellent degradation resistance ( Liu et al, 2022a ).…”
Section: Degradation Behavior and Typical Strategies To Enhance The C...mentioning
confidence: 99%
“…There are several approaches to increase the corrosion resistance of Mg and its alloys, including internal methods such as the modification of alloy composition/microstructure (fabrication of high-purity alloys, refinement of microstructure, etc.) [ 12 , 17 , 18 , 19 , 20 ]. The external methods include surface treatment and coating processes (electroplating, chemical conversion coating, electrochemical conversion coating, laser/ion or electron beam treatment, sol-gel coating, and organic coating, etc.)…”
Section: Introductionmentioning
confidence: 99%